Nutrient recovery from apple pomace waste by vermicomposting technology - Hanc, Ales; Chadimova, Zuzana (Bioresource technology, 2014)
The present work was focused on vermicomposting apple pomace waste and its mixtures with straw in volume proportions of 25%, 50%, and 75%. The feasibility was evaluated on the basis of agrochemical properties and earthworm biomass. Vermicomposting was able to reduce the weight and volume of the feedstock by 65% and 85%, respectively. The resulting vermicomposts were characterized by slightly acidic to neutral pH (5.9-6.9), and optimal EC (1.6-4.4mS/cm) and C:N ratios (13-14). The total content of nutrients increased during vermicomposting for all of the treatments with the following average final values: N=2.8%, P=0.85%, K=2.3%, and Mg=0.38%. The addition of straw to apple pomace did not enhance earthworm biomass, but did increase the available content of nutrients during vermicomposting. The data reveals that vermicomposting is a suitable technology for the decomposition of apple pomace waste into a value added product.
Keywords: draslík; hořčík; Nitrogen; dusík; elektrická vodivost; Potassium; biodegradace; fosfor; půda; Waste Products; zvířata; Biodegradation, Environmental; biomasa; Carbon; Phosphorus; Electric Conductivity; Vermicomposting; Hydrogen-Ion Concentration; odpadky - odstraňování; Apple pomace; Earthworms; Straw; Malus; Animals; Soil; Biomass; uhlík; odpadní produkty; koncentrace vodíkových iontů; Refuse Disposal; Magnesium; Oligochaeta